Psikologi Kognitif Islam - Alfian Gunawan; Khairil Anwar; Vivik Shofiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic cognitive psychology views human beings as entities possessing rational, emotional, and spiritual dimensions that are integrated through the intellect (ʿaql), soul (nafs), and heart (qalb). Unlike modern cognitive psychology, which emphasizes rational and empirical aspects, Islamic cognitive psychology places the qalb as the center of spiritual and moral consciousness, the intellect as an instrument for thinking and understanding truth, and the soul as the source of impulses, emotions, and behavioral tendencies. This study aims to analyze the concepts of intellect, soul, and heart, as well as their functional relationships in human cognitive processes from an Islamic perspective. The research employs a qualitative approach using a library research method based on the Qur’an, Hadith, and classical as well as contemporary literature on Islamic psychology. The findings indicate that the balance and integration of the intellect, soul, and heart play an important role in shaping consciousness, decision-making, and the quality of human personality. Therefore, Islamic cognitive psychology provides a comprehensive conceptual framework for understanding human mental processes and contributes to the development of mental health concepts grounded in spiritual and transcendental values.